Distributed Rs Coded Cooperation: Optimized Code Construction and Decoding by Critical SNR Aided - Chen, Chen; Yang, Fengfan; Zhao, Chunli; Waweru, Daniel Kariuki; Xu, HongJun (Wireless personal communications, 2023)
The novel distributed Reed-Solomon coded cooperative (DRSCC) scheme is presented in this manuscript to construct a promising resultant code with an improved code weight distribution at the destination terminal. To optimize relay cooperation, an exhausted search (ES) algorithm is proposed to select the optimal code. Based on this algorithm, the more practical reduced-complexity search (RCS) algorithm is then proposed. The results of Monte-Carlo simulations indicate that the bit error rate (BER) performance of DRSCC schemes utilizing the two algorithms is almost equivalent. Moreover, a novel joint decoding algorithm, namely Critical-SNR-Aided (CSA), is suggested and implemented to enhance overall performance at the destination. To generalize the proposed DRSCC scheme, multiple RS codes with varying lengths at the source and relay are investigated. Numerical simulations show that the proposed DRSCC scheme clearly outperforms the corresponding point-to-point RS-coded scheme by a BER gain of 3.6–3.8 dBs. Furthermore, the proposed DRSCC scheme outperforms some existing RS-coded cooperative schemes over the fast Rayleigh fading channel.